Cross-sectional and longitudinal associations between serum uric acid and metabolic syndrome: Results from Fangchenggang Area Male Health and Examination Survey in China - Chen, Dongni; Zhang, Haiying; Gao, Yong; Lu, Zheng; Yao, Ziting; Jiang, Yonghua; Lin, Xinggu; Wu, Chunlei; Yang, Xiaobo; Tan, Aihua; Mo, Zengnan (Clinica chimica acta, 2015)
It is controversial whether serum uric acid (SUA) is a risk factor for the prevalence of metabolic syndrome (MetS). The current study was designed to highlight the association of SUA and MetS and its components. Data on 3675 healthy male subjects, aged 17–88years, were collected for the cross-sectional study. A representative sample of 2575 individuals who did not suffer from MetS at baseline was involved in the cohort study. A cox regression model was applied to evaluate causality for the 2- and 4-year large scale longitudinal study. In the cross-sectional analysis, SUA showed a statistically significant negative correlation with high-density lipoprotein cholesterol (HDL-c) and a positive correlation with blood pressure (BP), triglycerides (TG), waist circumference (WC), and body mass index (BMI) (all P<0.001). In longitudinal analysis, examining the risk of developing MetS, SUA concentrations (hazard ratios comparing fourth quartile to the first quartile of 1.75; 95% CI, 1.26–2.41) were positively associated with incident MetS after adjusted for age, blood pressure, glucose, TG, HDL-c, smoking, alcohol drinking and education. SUA is positively correlated with the prevalence of MetS. Increased SUA concentration may be an independent risk factor for MetS. •The study is combined cross-sectional and longitudinal aspects.•The large sample size with a considerably high response rate guaranteed the reliability of our results.•We report SUA was independently positively correlated with the prevalence of MetS.•We report SUA may be a risk factor for MetS.